Strategies to reduce torque loss of abutment screws - Beatriz Pardal-Peláez; Javier Sanz-Alonso; José González-Serrano; Javier Montero-Martín (Wolters Kluwer Medknow Publications, 2018)
Aim: The loosening of abutment screws is a recurrent problem in oral implantology that lacks a consensual solution. The aim of this paper is to review the literature available in search for strategies that might lessen the torque loss of abutment screws. Materials and Methods: A bibliographic search was conducted in PubMed with the terms "dental implants AND (screw loosening or screw preload)," from which the papers proposing solutions to torque loss in abutment screws loosening in single implants were selected. Results: According to the review, our results are two folds. It has been found that there are, on the one hand, strategies that affect screw tightening (tightening 10 min after the first tightening and application of a torque value above that recommended by the manufacturer); and on the other hand, approaches that affect implant-prosthesis design and materials (connection, screw, and internal thread of the implant). Conclusion: Taking these findings into an account, it is possible to claim that torque loss is multifactorial in that there is no single valuable strategy for reducing screw loosening. Thus, materials and screw coatings, connection design, and appropriate clinical strategies should be carefully selected to minimize the torque loss, thereby increasing the durability of the implant prosthesis and the patient's quality of life.